Preconditions for Returning Highly-Profitable Shot Lots to Railway Transport - D. A. Bakunin; K. I. Shvedin; S. O. Litvintsev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article describes reasons for transition of small shipments from railway transport to automobile one and studies proposals to return highly-profitable shot lots back to the railway transport. Today we can observe a rise in the volume of shot lots and joint goods that are delivered by automobile transport. The authors analyzed global experience of transporting shot lots in mid-ton containers. Analysis of market of joint goods transporters showed that serious impact for choosing forwarder is exercised by speed of delivery. Study of existing technologies of goods transportation by speedy cargo trains was carried out, which showed the necessity to choose for shot lots transportation such technology, which could allow railway transport to compete with automobile one not only at long distances but at short legs as well. The authors proposed to use new intermodal transport cargo units: 5- and 10- foot mid-ton module and 10-and 20-foot pick-up body to transport shot lots. Issues of tariffing goods transportation in new intermodal transport units were analyzed and the use of through tariff rate was grounded.